Photoshop elements tips, tricks & shortcuts : in easy steps : for Windows and Mac 2020 edition - Vandome, Nick (In easy steps., 2020)
"2020 Photoshop Elements Tips, Tricks and Shortcuts in easy steps not only offers a comprehensive guide to getting up and running with the software, but goes further: providing a wealth of detail in ways to progress to more advanced photo-editing and also find some of the hidden secrets of the software. Although the book looks at some of the ways you can expand your photo-editing exploits, it does not forget new users or anyone who wants to brush up on the basics. Photoshop Elements Tips, Tricks and Shortcuts in easy steps covers versions for both PC and Mac users, and has something for everyone: an in depth introduction for new users, and a range of options for those who want to take their photo-editing to the next level. Throughout, there are hundreds of tips and handy hints so that the reader will feel like an Elements expert in no time."--Amazon.com.